2021
DOI: 10.1002/bab.2272
|View full text |Cite
|
Sign up to set email alerts
|

Biochanin‐A has antidiabetic, antihyperlipidemic, antioxidant, and protective effects on diabetic nephropathy via suppression of TGF‐β1 and PAR‐2 genes expression in kidney tissues of STZ‐induced diabetic rats

Abstract: One of the major complications of diabetes is diabetic nephropathy, and often many patients suffer from diabetic nephropathy. That is why it is important to find the mechanisms that cause nephropathy and its treatment. This study was designed to examine the antidiabetic effects of biochanin A (BCA) and evaluate its effects on oxidative stress markers and the expression of transforming growth factor‐β1 (TGF‐β1) and protease‐activated receptors‐2 (PAR‐2) genes in the kidney of type 1 diabetic rats. After inducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…This nicely matches the earlier reports that stated increased expression of PAR-2 in unilateral ureteral obstruction in mouse model (38) and in IgA nephropathy patients (39). Also, PAR-2 gene expression was found to be elevated in the kidney tissues of STZ-treated mice compared to normal rats (40). On the other side, pre-treatment of mice with DPSE or HM showed a significant decrease of PAR-2 compared to the Gen-treated group suggesting that the observed nephroprotective effect of both extracts might be mediated by inhibition of PAR-2.…”
Section: Discussionsupporting
confidence: 92%
“…This nicely matches the earlier reports that stated increased expression of PAR-2 in unilateral ureteral obstruction in mouse model (38) and in IgA nephropathy patients (39). Also, PAR-2 gene expression was found to be elevated in the kidney tissues of STZ-treated mice compared to normal rats (40). On the other side, pre-treatment of mice with DPSE or HM showed a significant decrease of PAR-2 compared to the Gen-treated group suggesting that the observed nephroprotective effect of both extracts might be mediated by inhibition of PAR-2.…”
Section: Discussionsupporting
confidence: 92%
“…The inhibition of PAR-2 has been found to enhance autophagy while preventing inflammation and fibrosis [86]. Contrary to expectations, biochanin A mitigates diabetic nephropathy by downregulating the expression of the TGF-β1 and PAR-2 genes [65,81,82]. Among the numerous health benefits of isoflavones, biochanin A is widely recognized for its anti-inflammatory, antihyperlipidemic, antioxidant, and anticancer attributes by suppressing TGF-β1 and PAR-2 gene expression in kidney tissues of STZ-induced diabetic rats [80][81][82].…”
Section: Anti-diabetic Activitymentioning
confidence: 99%
“…Investigations conducted in laboratory settings as well as on living organisms have shown that myricitrin can mitigate oxidative stress by stimulating nuclear factor erythroid 2-related factor 2 (Nrf-2) and counteracting oxidative radicals effectively (Figure 4) [72,79]. Among the numerous health benefits of isoflavones, biochanin A is widely recognized for its anti-inflammatory, antihyperlipidemic, antioxidant, and anticancer attributes by suppressing TGF-β1 and PAR-2 gene expression in kidney tissues of STZ-induced diabetic rats [80][81][82]. In addition to its antioxidant properties, biochanin A appears to exert an anti-diabetic influence.…”
Section: Anti-diabetic Activitymentioning
confidence: 99%
“…Biochanin A could be a promising candidate for lowering the advancement of cardiomyopathy in people with type 2 diabetes (Oza and Kulkarni, 2022). A study designed to examine the diabetic and diabetic nephropathy effects on diabetic rats revealed that administering biochanin-A markedly reduced the expression of transforming growth factor-β1 (TGF-β1), protease-activated receptors 2 (PAR-2) genes, and fasting blood glucose (FBG) (Amri et al, 2021).…”
Section: Metabolic Disorders 221 Diabetesmentioning
confidence: 99%